Exogenous application of a low concentration of melatonin enhances salt tolerance in rapeseed (Brassica napus L.) seedlings - Liu ZENG; Jun-song CAI; Jing-jing LI; Guang-yuan LU; Chun-sheng LI; Gui-ping FU; Xue-kun ZHANG; Hai-qing MA; Qing-yun LIU; Xi-ling ZOU; Yong CHENG (Journal of Integrative Agriculture)
Melatonin is a naturally occurring compound in plants. Here, we tested the effect of exogenous melatonin on rapeseed (Brassica napus L.) grown under salt stress. Application of 30 µmol L−1 melatonin alleviated salt-induced growth inhibition, and the shoot fresh weight, the shoot dry weight, the root fresh weight, and the root dry weight of seedlings treated with exogenous melatonin increased by 128.2, 142.9, 122.2, and 124.2%, respectively, compared to those under salt stress. In addition, several physiological parameters were evaluated. The activities of antioxidant enzymes including peroxidase (POD), catalase (CAT) and ascorbate peroxidase (APX) were enhanced by 16.5, 19.3, and 14.2% compared to their activities in plants without exogenous melatonin application under salt stress, while the H2O2 content was decreased by 11.2% by exogenous melatonin. Furthermore, melatonin treatment promoted solute accumulation by increasing the contents of proline (26.8%), soluble sugars (15.1%) and proteins (58.8%). The results also suggested that higher concentrations (>50 µmol L−1) of melatonin could attenuate or even prevent the beneficial effects on seedling development. In conclusion, application of a low concentration of exogenous melatonin to rapeseed plants under salt stress can improve the H2O2-scavenging capacity by enhancing the activities of antioxidant enzymes such as POD, CAT and APX, and can also alleviate osmotic stress by promoting the accumulation of osmoregulatory substances such as soluble proteins, proline, and water soluble glucan. Ultimately, exogenous melatonin facilitates root development and improves the biomass of rapeseed seedlings grown under salt stress, thereby effectively alleviating the damage of salt stress in rapeseed seedlings.